Salah urus risiko dalam projek pembangunan projek perumahan: kajian ke atas projek perumahan terbengkalai di Malaysia - Rusli, Norharnila (2006)
Risk and uncertainty can potentially damage construction project. Hence, risk management is an important part in construction companies’ decision making process. It’s very useful for the parties involved in construction industry. This study reviews the housing industry and risk involved with a particular reference to housing. Housing industry which is a part of construction industry is also exposed to various form of risk that may affect the project throughout the life cycle of the project. As abandoned projects can cause loss to customers, this study also reviews statistics on abandoned housing project in Malaysia. The interviews have been carried out and data have been collected from the Ministry of Local Government and Housing. The data includes the categories of abandoned project and factors that lead to the abandonment of the projects. The data was summarised using simple statistical methods. The finding of the study indicates that financial was the main risk in housing development. The study also highlights other significant risks upon which the findings of the study will provide a basis for strategies to minimise risks in housing projects.